Preparation method and application of gel-loaded high-entropy compound
Through the preparation method of gel-supported high-entropy compounds, the problem of low electrocatalytic depolymerization conversion in the prior art was solved, and efficient electrocatalytic degradation was achieved, with a conversion rate greater than 99%.
Patent Information
- Application Number
- CN202411787765.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively catalyze the dissolution of lignin, resulting in a low conversion rate.
The preparation method of gel-supported high-entropy compounds is adopted to prepare the catalyst through ultrasonic treatment, microwave treatment and calcination, and adhere it to the electrode or insert it into an electrolytic solvent to achieve electrocatalytic degradation of lignin.
High-efficiency electrocatalytic degradation of lignin is achieved, with a conversion rate greater than 99%. The dispersion and specific surface area of the catalyst are improved by introducing gel, thereby improving the efficiency of electrocatalytic depolymerization.
Smart Images

Figure CN119530878A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrocatalysis and more specifically relates to a preparation method and application of a gel-supported high entropy compound. Background Art
[0002] Renewable biomass resources play a vital role in solving human production and living needs and environmental problems. Lignin is a complex organic compound present in plant cell walls, composed of phenyl and propylene monomers connected by phenols. It plays a role of structural support and protection in plants. In recent years, studies have found that lignin not only plays an important role in nature, but its depolymerization is also of great significance in the field of organic chemical synthesis and biofuels. As a natural polymer substance, lignin is a biomass resource rich in aromatic structures and can be used as a renewable precursor for value-added products. Various low molecular weight organic compounds can be obtained by depolymerizing lignin, which can provide rich raw materials for organic synthesis, realize the efficient utilization of wood resources, and promote sustainable development. Summary of the invention
[0003] An object of the present invention is to solve at least the above problems and to provide at least the advantages which will be described hereinafter.
[0004] Another object of the present invention is to provide a method for preparing a gel-supported high entropy compound, wherein the prepared catalyst has a good catalytic effect on lignin.
[0005] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a gel-loaded high entropy compound is provided, which comprises the following steps: 1) Take 5-9 kinds of metal salts, dissolve them in aqueous solution, mix them, and obtain an equiatomic precursor solution; 2) adding an initiator and a polymer monomer to an equiatomic precursor solution, and ultrasonically treating the solution to obtain an ultrasonically treated solution; 3) The ultrasonic treatment liquid is subjected to microwave treatment, drying, and calcination to obtain a gel-loaded high entropy compound.
[0006] Preferably, the metal salt is a nitrate, sulfate or acetylacetonate of iron, cobalt, nickel, copper, zinc, chromium, magnesium, manganese, aluminum, cerium, samarium or bismuth.
[0007] Preferably, the initiator may be one of ammonium persulfate and potassium persulfate; the polymer monomer may be one of acrylic acid, betaine and phosphorylcholine.
[0008] Preferably, the microwave treatment is performed for 5-30 min; the drying temperature is 60-120° C., the drying time is 8-24 h; and the calcination temperature is 200-800° C.
[0009] A method for preparing a catalytic electrode comprises the following steps: 1) Take 5-9 kinds of metal salts, dissolve them in aqueous solution, mix them, and obtain an equiatomic precursor solution; 2) adding an initiator and a polymer monomer to an equiatomic precursor solution, and ultrasonically treating the solution to obtain an ultrasonically treated solution; 3) The ultrasonic treatment liquid is subjected to microwave treatment to obtain a microwave-treated product; 4) Inserting an electrode into the microwave-treated object, taking it out after it has rested, and drying it to obtain the catalytic electrode.
[0010] A method for electrocatalytic depolymerization of lignin using a gel-supported high entropy compound comprises the following steps: 1) attaching the gel-loaded high entropy compound to an electrode, or inserting the catalytic electrode into an electrolytic solvent; 2) Add lignin, electrolyte and catalyst into the electrolytic solvent and apply power to the electrodes to achieve electrocatalytic degradation of lignin.
[0011] Preferably, the co-catalyst is tert-butyl hydroperoxide.
[0012] Preferably, the electrolyte is tetrabutylammonium hydroxide.
[0013] Preferably, the current applied is 5-50 mA.
[0014] The present invention includes at least the following beneficial effects: First, the high entropy compound prepared by the method of the present invention is used as a catalyst, and the electrocatalytic depolymerization conversion rate of lignin is greater than 99%, which can efficiently electrocatalytically degrade lignin.
[0015] Second, when preparing high entropy compounds, the method of the present invention helps to improve the dispersion of high entropy compounds by introducing gel, so that the particle size of the prepared high entropy compound catalyst is smaller and has a larger specific surface area, thereby increasing the conversion rate of electrocatalytic depolymerization. Third, the present invention inserts the electrode into the colloid after microwave treatment, takes it out after standing, and dries it by drying or air drying it naturally. The operation is simple, and a good adhesion effect is achieved, while also improving the conversion rate of electrocatalytic depolymerization.
[0016] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the conversion rate diagram of the electrocatalytic depolymerization of the lignin model molecule benzyl phenyl ether at different times; Figure 2 This is the conversion rate diagram of the electrocatalytic depolymerization of lignin model molecule benzyl phenyl ether at different currents; Figure 3 This is the conversion rate diagram of the electrocatalytic depolymerization of benzyl phenyl ether, a model lignin molecule, in methanol and acetonitrile; Figure 4 This is the graph showing the conversion rate of electrocatalytic depolymerization of lignin model molecule benzyl phenyl ether with or without a catalyst; Figure 5 The graph shows the electrocatalytic depolymerization conversion rate of different lignin model molecules; Figure 6 is the electrocatalytic depolymerization conversion diagram with and without catalyst; Figure 7 Graph showing the electrocatalytic depolymerization conversion rate of high entropy compound catalysts with and without gel loading; wherein, the high entropy without loading is the catalyst prepared by <Comparative Example 1>, loaded on the electrode by the method of <Example 4>; the high entropy with gel loading is the electrode prepared by <Example 5>; Figure 8 The graph is a graph of the electrocatalytic depolymerization conversion rate of electrodes prepared by different preparation methods; wherein, the electrode processed under gel state is the electrode prepared in Example 5, and the electrode processed under powder state is the electrode prepared in Example 4. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0019] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0020] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.
[0021] The present invention provides a method for preparing a gel-loaded high entropy compound, which comprises the following steps: 1) Take 5-9 kinds of metal salts, dissolve them in aqueous solution, mix them, and obtain an equiatomic precursor solution; 2) adding an initiator and a polymer monomer to an equiatomic precursor solution, and ultrasonically treating the solution to obtain an ultrasonically treated solution; 3) The ultrasonic treatment liquid is subjected to microwave treatment, drying, and calcination to obtain a gel-loaded high entropy compound.
[0022] In another technical solution, the metal salt is a nitrate, sulfate or acetylacetonate of iron, cobalt, nickel, copper, zinc, chromium, magnesium, manganese, aluminum, cerium, samarium or bismuth.
[0023] In another technical solution, the initiator may be one of ammonium persulfate and potassium persulfate; the polymer monomer may be one of acrylic acid, betaine, and phosphorylcholine; the betaine may be carboxybetaine or sulfonamide betaine.
[0024] In another technical solution, the microwave treatment is 5-30 min; the drying temperature is 60-120 °C, the drying time is 8-24 h; and the calcination temperature is 200-800 °C.
[0025] A method for preparing a catalytic electrode comprises the following steps: 1) Take 5-9 kinds of metal salts, dissolve them in aqueous solution, mix them, and obtain an equiatomic precursor solution; 2) adding an initiator and a polymer monomer to an equiatomic precursor solution, and ultrasonically treating the solution to obtain an ultrasonically treated solution; 3) The ultrasonic treatment liquid is subjected to microwave treatment to obtain a microwave-treated product; 4) Inserting an electrode into the microwave-treated object, taking it out after it has rested, and drying it to obtain the catalytic electrode.
[0026] A method for electrocatalytic depolymerization of lignin using a gel-supported high entropy compound comprises the following steps: 1) attaching the gel-loaded high entropy compound to an electrode, or inserting the catalytic electrode into an electrolytic solvent; 2) Add lignin, electrolyte and catalyst into the electrolytic solvent and apply power to the electrodes to achieve electrocatalytic degradation of lignin.
[0027] In another technical solution, the co-catalyst is tert-butyl hydroperoxide.
[0028] In another technical solution, the electrolyte is tetrabutylammonium hydroxide.
[0029] In another technical solution, the current is 5-50 mA.
[0030] <Example 1> A method for preparing a gel-loaded high entropy compound comprises the following steps: 1) Weigh 10 mmol of metal nitrates, specifically cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, and iron nitrate nonahydrate, respectively, and dissolve them in 10 mL of distilled water. Mix the five solutions evenly to obtain an equiatomic precursor solution. 2) Add 0.1 g of initiator ammonium persulfate and 15 g of polymer monomer acrylic acid to the equiatomic precursor solution, stir and dissolve, add NaOH to adjust the pH to 8, and perform ultrasonic treatment for 5 min to obtain an ultrasonic treatment solution; 3) The ultrasonic treatment liquid was treated with microwave for 15 min, dried in an oven at 80 °C for 12 h, and then placed in a muffle furnace and heated from room temperature to 230 °C at a heating rate of 2 °C / min. After keeping the temperature for 1 h, it was taken out and cooled. The obtained sample was ground into powder to obtain a gel-loaded high entropy compound.
[0031] <Example 2> A method for preparing a gel-loaded high entropy compound comprises the following steps: 1) Weigh 10 mmol of metal nitrates, specifically cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, iron nitrate nonahydrate, manganese sulfate, bismuth nitrate, cerium sulfate and magnesium sulfate heptahydrate, respectively, and dissolve them in 10 mL of distilled water. Mix the nine solutions evenly to obtain an equiatomic precursor solution. 2) Add 0.1 g of initiator ammonium persulfate and 15 g of polymer monomer carboxy betaine to the equiatomic precursor solution, stir to dissolve, and ultrasonically treat for 5 min to obtain an ultrasonically treated solution; 3) The ultrasonic treatment liquid was treated with microwave for 15 min, dried in an oven at 80 °C for 12 h, and then placed in a muffle furnace and heated from room temperature to 230 °C at a heating rate of 2 °C / min. After keeping the temperature for 1 h, it was taken out and cooled. The obtained sample was ground into powder to obtain a gel-loaded high entropy compound.
[0032] <Example 3> A method for preparing a gel-loaded high entropy compound comprises the following steps: 1) Weigh 10 mmol of metal nitrates, specifically cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, iron nitrate nonahydrate, manganese sulfate, samarium acetylacetonate, chromium sulfate and magnesium sulfate heptahydrate, respectively, and dissolve them in 10 mL of distilled water. Mix the nine solutions evenly to obtain an equiatomic precursor solution. 2) Add 0.1 g of initiator ammonium persulfate and 15 g of polymer monomer phosphorylcholine to the equiatomic precursor solution, stir to dissolve, and ultrasonically treat for 5 min to obtain an ultrasonically treated solution; 3) The ultrasonic treatment liquid was treated with microwave for 15 min, dried in an oven at 80 °C for 12 h, and then placed in a muffle furnace and heated from room temperature to 230 °C at a heating rate of 2 °C / min. After keeping the temperature for 1 h, it was taken out and cooled. The obtained sample was ground into powder to obtain a gel-loaded high entropy compound.
[0033] <Example 4> A method for preparing a catalytic electrode, specifically comprising: 5 mg of the high entropy compound electrocatalyst prepared in Example 1 and 1 mg of conductive carbon black were dispersed in a mixed solution of 200 ul of water, 700 ul of ethanol and 30 ul of 5% Nafion solution (perfluororesin solution), and ultrasonically treated for 30 min until the mixture was uniform. A few microliters were taken up with a pipette and dripped onto the electrode surface drop by drop, and naturally air-dried to obtain the catalytic electrode.
[0034] <Example 5> A method for preparing a catalytic electrode comprises the following steps: 1) Weigh 10 mmol of metal nitrates, specifically cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, and iron nitrate nonahydrate, respectively, and dissolve them in 10 mL of distilled water. Mix the five solutions evenly to obtain an equiatomic precursor solution. 2) Add 0.1 g of initiator ammonium persulfate and 15 g of polymer monomer acrylic acid to the equiatomic precursor solution, stir and dissolve, adjust pH to 8 with NaOH, and perform ultrasonic treatment for 5 min to obtain an ultrasonic treatment solution; 3) The ultrasonic treatment liquid is subjected to microwave treatment for 15 minutes, and an electrode is inserted into the colloid after microwave treatment. After standing for 5 minutes, the electrode is taken out, and the electrode is hung and naturally air-dried to obtain the catalytic electrode.
[0035] <Example 6> A method for electrocatalytic depolymerization of lignin using a gel-loaded high entropy compound comprises the following steps: 1) inserting the catalytic electrode obtained in <Example 5> into an acetonitrile solvent; 2) Add 0.02 M benzyl phenyl ether, 0.01 M tetrabutylammonium hydroxide, and 0.5 M tert-butyl hydroperoxide to the electrolytic solvent, apply power to the electrodes, and the working current is 25 mA to achieve electrocatalytic degradation of the lignin model molecule benzyl phenyl ether.
[0036] <Effect Test> 1. Effect of electrolysis time on electrocatalytic conversion rate The method of <Example 6> was used to investigate the effect of different time on the electrocatalytic conversion rate of benzyl phenyl ether. The results are as follows: Figure 1 As shown. Figure 1 The results showed that the degradation rate of benzyl phenyl ether exceeded 95% after 50 min of electrocatalytic degradation.
[0037] 2. Effect of electrolysis current on electrocatalytic conversion rate The method of <Example 6> was used to investigate the effect of different working currents on the electrocatalytic conversion rate of benzyl phenyl ether. The results are as follows: Figure 2 As shown. Figure 2The results show that as the working current increases, the conversion rate also increases rapidly.
[0038] 3. Effect of electrolytic solvent on electrocatalytic conversion rate The method of <Example 6> was used to investigate the effect of different solvents on the electrocatalytic conversion rate of benzyl phenyl ether. The results are as follows: Figure 3 As shown. Figure 3 The results show that the conversion rate of acetonitrile as a solvent is better than that of other solvents such as acetone.
[0039] 4. Effect of promoter on electrocatalytic conversion rate The method of <Example 6> was used to investigate the effect of the presence or absence of tetrabutylammonium hydroxide as a co-catalyst on the electrocatalytic conversion rate of benzyl phenyl ether. The results are as follows: Figure 4 As shown. Figure 4 The results show that tetrabutylammonium hydroxide co-catalyst can improve the electrocatalytic conversion rate.
[0040] 5. Effect of lignin type on electrocatalytic conversion rate The method of <Example 6> was used to investigate the effect of lignin type on the electrocatalytic conversion rate of benzyl phenyl ether. The results are as follows: Figure 5 As shown. Figure 5 The results show that the electrocatalytic conversion rates of benzyl phenyl ether and diphenylethanol are significantly higher than that of PP-ol.
[0041] 6. Effect of Catalyst on Electrocatalytic Conversion Rate The method of <Example 6> is used, which is different from <Example 6> in that the catalyst prepared by the present invention is not loaded on the electrode, and is used for electrocatalytic degradation of lignin. The results are as follows Figure 6 As shown. Figure 6 The results show that when no catalyst is loaded on the electrode, lignin is hardly degraded.
[0042] 7. Effect of gel on catalyst particle size Comparative Example 1: A method for preparing a gel-loaded high entropy compound, comprising the following steps: 1) Weigh 10 mmol of metal nitrates, specifically cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, zinc nitrate hexahydrate, and iron nitrate nonahydrate, respectively, and dissolve them in 10 mL of distilled water. Mix the five solutions evenly to obtain an equiatomic precursor solution. 2) The solution pH was adjusted to 8, and the solution was stirred at a constant temperature of 80°C for 12 h on a magnetic stirrer. After drying in an oven at 80°C for 12 h, the solution was placed in a muffle furnace and heated from room temperature to 230°C at a heating rate of 2°C / min. After keeping the temperature for 1 h, the solution was taken out and cooled. The obtained sample was ground into powder to obtain a high entropy compound catalyst.
[0043] The grinding method is the same as in Example 1, and the particle size of the obtained catalyst is shown in Table 1 below.
[0044] Table 1 Catalyst particle size Particle size (nm) Comparative Example 1 105 Example 1 35 From the results in Table 1, it can be seen that the present invention helps to disperse the catalyst by adding gel, so that the prepared particle size is smaller, which helps to increase the specific surface area of the catalyst and improve the electrocatalytic conversion rate.
[0045] 8. Effect of gel on electrocatalytic conversion rate The method of <Example 6> was used, except that the catalyst prepared in <Comparative Example 1> was used on the electrode and loaded on the electrode using the method of <Example 4>. Figure 7 As shown. Figure 7 The results show that gel-loaded high entropy compounds can significantly improve the electrocatalytic conversion rate.
[0046] IX. Effect of electrode preparation method on electrocatalytic conversion efficiency The method of <Example 6> was used, and the difference from <Example 6> was that the electrode was the electrode prepared in <Example 4>. Figure 8 As shown. Figure 8 The results show that the electrode prepared by inserting the electrode into the colloid after microwave treatment can further improve the electrocatalytic depolymerization conversion rate of lignin.
[0047] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a gel-loaded high entropy compound, characterized in that: The following steps are involved: 1) Take 5-9 kinds of metal salts, dissolve them in aqueous solution, mix them, and obtain an equiatomic precursor solution; 2) adding an initiator and a polymer monomer to an equiatomic precursor solution, and ultrasonically treating the solution to obtain an ultrasonically treated solution; 3) The ultrasonic treatment liquid is subjected to microwave treatment, drying, and calcination to obtain a gel-loaded high entropy compound.
2. The method for preparing a gel-supported high entropy compound according to claim 1, characterized in that: The metal salt is a nitrate, sulfate or acetylacetonate of iron, cobalt, nickel, copper, zinc, chromium, magnesium, manganese, aluminum, cerium, samarium or bismuth.
3. The method for preparing a gel-supported high entropy compound according to claim 1, characterized in that: The initiator can be one of ammonium persulfate and potassium persulfate; the polymer monomer can be one of acrylic acid, betaine and phosphorylcholine.
4. The method for preparing a gel-supported high entropy compound according to claim 1, characterized in that: Microwave treatment for 5-30 min; drying temperature of 60-120 ℃, drying time of 8-24 h; calcination temperature of 200-800 ℃.
5. A method for preparing a catalytic electrode, characterized in that: The following steps are involved: 1) Take 5-9 kinds of metal salts, dissolve them in aqueous solution, mix them, and obtain an equiatomic precursor solution; 2) adding an initiator and a polymer monomer to an equiatomic precursor solution, and ultrasonically treating the solution to obtain an ultrasonically treated solution; 3) The ultrasonic treatment liquid is subjected to microwave treatment to obtain a microwave-treated product; 4) Inserting an electrode into the microwave-treated object, taking it out after it has rested, and drying it to obtain the catalytic electrode.
6. A method for electrocatalytic depolymerization of lignin using a gel-supported high entropy compound, characterized in that: The following steps are involved: 1) Attaching the gel-supported high entropy compound described in claim 1 to an electrode, or inserting the catalytic electrode described in claim 5 into an electrolytic solvent; 2) Add lignin, electrolyte and catalyst into the electrolytic solvent and apply power to the electrodes to achieve electrocatalytic degradation of lignin.
7. The method for electrocatalytic depolymerization of lignin using a gel-supported high entropy compound according to claim 6, characterized in that: The catalyst is tert-butyl hydroperoxide.
8. The method for electrocatalytic depolymerization of lignin using a gel-supported high entropy compound according to claim 6, characterized in that: The electrolyte is tetrabutylammonium hydroxide.
9. The method for electrocatalytic depolymerization of lignin using a gel-supported high entropy compound according to claim 6, characterized in that: The current through the power supply is 5-50 mA.
Citation Information
Cited By
High-entropy sulfide catalyst, preparation method thereof and lignin depolymerization electro-catalysis method
CN121610827A